Cinema Africa 24/25: A Conversation with Mo Harawe, director of "The Village next to Paradise" (Cinema Africa 2024/25, 2026)
In this interview, director Mo Harawe discusses his debut feature film "The Village Next to Paradise", presented at the Cinema Africa Festival 2024–2025 in Bayreuth. In conversation with Prof. Dr. Ute Fendler, organiser and curator of the festival, Harawe reflects on the film’s portrayal of family life in a rural Somali village shaped by economic hardship, environmental pressures and the lingering effects of conflict. He also discusses his approach to storytelling, his use of non-professional actors, and his intention to foreground everyday experiences beyond dominant narratives. The interview was recorded as part of the 16th edition of the Cinema Africa Festival, organised by the Africa Multiple Cluster of Excellence at the University of Bayreuth.